Molecular solar thermal energy storage in photoswitch oligomers increases energy densities and storage times - Mads Mansø (Nature Portfolio, 2018)
Molecular solar thermal systems are promising for storing solar energy but achieving high energy storage densities and absorption characteristics matching the solar spectrum is challenging. Here the authors present a design strategy for electronically coupled photoswitches which allow for high energy density storage for solar energy storage applications.